A mechano-biocatalytic one-pot approach to release sugars from lignocellulosic materials - Zhong, Yuan (2020)
A novel, mechano-biocatalytic one-pot process was developed by this study to efficiently release monosaccharides from lignocellulosic materials in an environmentally-friendly manner. The process synergistically integrates ball milling and enzymatic hydrolysis to complete pretreatment and hydrolysis of lignocellulosic materials in a single step without chemical supplements. High sugar titer and conversion from lignocellulosic materials were simultaneously achieved. Among four studied feedstocks (solid digestate, corn stover, switchgrass, and miscanthus), corn stover demonstrated much better sugar concentration and conversion. Under the preferred reaction condition, the glucose concentration reached 55.20 g/L with a glucose conversion of 88.63%. The corresponding xylose concentration was 20.06 g/L with a xylose conversion of 67.34%. The energy and exergy analyses further indicate that the studied process had better energy and exergy profiles than the conventional combined hydrolysis process. The average energy consumption of the mechano-biocatalytic process for four feedstocks was 1.05 kWh-e/kg dry biomass that was 56% lower than the average energy consumption (2.37 kWh-e/kg dry biomass) of the conventional process. The corresponding average exergy efficiency of the mechano-biocatalytic process was 67% that was much higher than the average efficiency (52%) of the conventional process. These results show that the mechano-biocatalytic one-pot process as an environmentally friendly approach can significantly simplify the pretreatment and hydrolysis and enhance their efficiencies for advanced fuel and chemical production.